European police recruits’ views on ideal personal characteristics of a police officer - Inzunza, Miguel (Policing and society, 2020)
As societies are becoming more heterogeneous and complex, the role of the police is becoming more demanding. To fulfil this role, police officers need several widely recognised skills and personal qualities, but less is known about how they are valued by police recruits. Thus, we have examined views of police recruits in six European countries on three competencies or characteristics of known importance for police work: knowledge, leadership, and the ability to form good relations with citizens. We have also explored variations in views of recruits in different organisations and changes in their views during their training. For these purposes, we used survey data collected in the RECPOL project. Since the data were collected from different populations and at different times, the analysis is based on measurement invariance methodology, and one of the aims was to highlight the importance of rigorous appraisal of the quality and comparability of similar survey data using such methods. The results reveal both differences and similarities in views of recruits in the surveyed countries and changes during training. Police culture appears to be a significant factor, as more items in the applied instrument could be validly used in comparisons of recruits in organisations with similar police traditions. The results also showed interesting contrasts, e.g. new recruits in Sweden rated good relations with citizens more highly than recruits in organisations with a more military history, but this pattern changed during training, presumably due to influences of the recruitment process, training and culture within the organisations.